Biomechanical differences during a jump cut motion in those with and without a concussion history. Issue 11 (25th May 2017) - Lapointe, Andrew P; Nolasco, Luis; Sosnowski, Aniela; Andrews, Eva; Martini, Douglas N; Gates, Deanna H; Broglio, Steven P
Abstract : Objective: To evaluate differences in biomechanics between young adult participants with and without a history of concussion during a jump cut manoeuvre. Design: Case control Setting: Laboratory Subjects: 7 controls (4 males, 3 females) and 7 concussed (4 males, 3 females) subjects, between the ages of 18 and 26, capable of engaging in a jump cut motion. Concussed subjects were tested on average 2.4 years post injury (SD=0.23 years). Intervention: Participants jumped forward with both feet onto a force platform landing on their dominant leg, and directed their cut in response to the centre arrow of the Flanker task. A total five trials were performed. Kinematic variables were captured during the manoeuvres via motion capture. Outcome measures: Peak knee flexion, abduction, and axial rotation Results: Concussed subjects showed lower peak flexion of the knee on their non-dominant leg [F=25.455, p<0.01, R=0.240] and greater peak external rotation of the knee on their dominant leg [F=9.97, p<0.01, R=0.145]. Concussed subjects also showed a lower vertical centre of mass during the task [F=9.985, p<0.05, R=0.119]. Conclusions: There is a growing body of literature linking orthopaedic injury in those no longer displaying the acute signs and symptoms of concussion. This is the first study evaluating kinematic changes with findings demonstrating kinematic abnormalities long after clinical signs and symptoms have passed. Competing interests: This project was funded by the Carl and Joan Kreager research fund. None.